Perancangan Dashboard IT Helpdesk pada PT. XYZ - Muhammad Raditya Vivaldy (Publikasi Indonesia, 2023)
The helpdesk dashboard functions to monitor: the number of tickets available, the average handling time for each ticket, module, system, or application that gets the most tickets, the department that submits tickets the most, which is adjusted to the needs of the helpdesk of PT. XYZ. Ticket is a trouble ticket or problem report that is used in an organization to detect, report, and provide solutions to various types of problems. In this thesis, the authors create a data mart using Kimball's nine-step methodology. Before designing the IT helpdesk dashboard, PT. XYZ. will be processed first using data integration tools, namely Pentaho. Helpdesk data will go through a three-phase process, namely (i) extract, (ii) transform, and (iii) load (ETL). The data will then be loaded into the data mart and processed into a data cube. Data cube is a tool that describes technology using a multi-dimensional image of a number of data to provide faster access to strategic information with the aim of speeding up analysis. The data cube will be visualized using an interactive dashboard design tool, namely Grafana.